A participação do usuário no processo de projeto de habitação de interesse social em sistemas autogestionários - Clarissa Maria Valgas e Bastos (2007)
This research studies the users participation in the process of development of a project of social housing in self-management systems in the city of Belo Horizonte. On-going enterprises were analyzed. They were generated by the resources of the Programa Crédito Solidário a low-income housing credit program created by the Brazilian federal government in 2004 - in partnership with the City Hall. The self-management system is relatively new in the city and we can say that the three agents involved in it the government, the technicalsupport and the beneficiaries´ associations - are currently on a learning phase. One of the justifications for this research is based on the assumption that a systematized register of these experiences can contribute to the gradual improvement of the process. The participativeprocess in architecture is investigated, considering the architectural project as a cultural product and analyzing it in the predominant specialization scene since the Modern Movement. Also some discussions on the participative architectural project are revised, including questions about the social housing project. Moreover, the management systems of the housing production of the City Hall of Belo Horizonte are presented, detailing the self-managementprocess. The research is developed by case studies of four enterprises assisted by different technical teams to make it possible to learn some of the methodologies used in the participative process and their results. Three of these settings are assisted by private architecture offices, which work under regular market conditions. They are the focus of thiswork. The fourth setting is assisted by a private office which is linked to an educational institution, thus presenting a counterpoint. Documentary researches and half-structured interviews for the collection of data were made. After these collections we analyzed some successes and difficulties of the Programa Crédito Solidário as well as those of theparticipative processes. We conclude that the users´ participation in the architectural project finds some impediments in the structure of the program and also on the processes of its development. In spite of the identified difficulties, however, we observe that the ProgramaCrédito Solidário represents an advance in the panorama of production of social housing and that the participation, if added to satisfactory structural conditions and reflections as well as questioning of traditional practice, can bring transformations to the social housing project towards the conception of spaces which includes the users real necessities.